Molecular Docking of the Bioactive Compound Physalis angulata as an Activator of Superoxide Dismutase 1 - Wilujeng, Retno; Harlina, Eva; Purwono, Rini Madyastuti; Andrianto, Dimas (Indonesian Journal of Applied Research (IJAR), 2025)
Physalis angulata was known for its pharmacological potential, including antioxidant activity, yet the specific bioactive compounds responsible for enhancing endogenous antioxidant enzymes, such as superoxide dismutase 1 (SOD 1), remained unclear. This study aimed to identify and evaluate the active compounds of P. angulata as natural SOD 1 activators using an In silico molecular docking approach. Forty-nine ligands derived from the active constituents of P. angulata were screened based on Lipinski’s Rule of Five and ADMET properties. Molecular docking was performed using the SOD 1 protein (PDB ID: 5YTO), and docking validation yielded an RMSD value of 0.005 Å. Among the test ligands, withanolide exhibited the most favorable binding energy (−7.011 kcal/mol) and the lowest inhibition constant (7.0 pM), forming strong interactions with key catalytic residues of the enzyme. These findings indicated that withanolide had promising potential as a natural SOD 1 activator, providing a basis for future antioxidant drug discovery.